THE IMPORTANCE OF MUSIC EDUCATION IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Ravi Appadao (International Journal of Literature and Language Studies, 2023)
This article discusses the importance of teaching music methodology in preschool educational institutions, methods of developing children’s musical abilities, and the organization of music lessons. It also highlights the effectiveness of using game-based and interactive methods in music education.